(untitled) (Strathmore Law Journal, 2023)
Custodial congestion still persists as one of the biggest challenges to Nigeria’s Criminal Justice System. This is attributed to the operation ineptitudes of the Nigerian police force which employs means such as holding charges. This paper examines the practice of holding charges in Nigeria as a major contributor to the congestion of correctional facilities in Nigeria. This paper contends that the practice of holding charges is unconstitutional; in violation of the principles of fair hearing; and presumption of innocence and merely a means of administrative expediency. This paper concludes that the practice of holding charge in Nigeria undermines the rights of accused persons and calls for urgent reforms to the Nigerian criminal justice system to ensure that the protection of human rights is in tandem with the basic international human rights laws which mandate States to respect and ensure everybody’s right to personal liberty and security, and therefore, proffer some policy recommendations.